Prevalence and molecular insights into carbapenem resistance: a 2-year retrospective analysis of superbugs in South India - Lathakumari, Rahul Harikumar; Vajravelu, Leela Kakithakara; Thulukanam, Jayaprakash; Nair, Dakshina M.; Vimala, Poornima Baskar; Panneerselvam, Vishnupriya (Frontiers in Medicine, 2025)
BackgroundCarbapenem-resistant Gram-negative bacteria (CR-GNB) pose a serious global health threat, especially in low- and middle-income countries. Local surveillance is crucial for informing antimicrobial stewardship and infection control strategies. This study aimed to evaluate the prevalence, demographic distribution, and temporal fluctuations of carbapenem resistance among key Gram-negative pathogens in a South Indian tertiary care center over a two-year period.MethodsA retrospective study was conducted on 8,359 non-duplicate Gram-negative isolates obtained from clinical specimens between July 2022 and July 2024. Organisms were identified, and antimicrobial susceptibility was determined using the VITEK® 2 Compact system (BioMérieux). Resistance to imipenem (IPM) and meropenem (MEM) was assessed. Data were stratified by age, sex, ward type, specimen source, and quarterly distribution. A subset of resistant isolates underwent molecular screening for carbapenemase genes using real time PCR.ResultsCarbapenem resistance was observed in 24% (2007) of Gram-negative isolates. Acinetobacter baumannii (48.0%) and Klebsiella pneumoniae (38.6%) accounted for the majority of resistant cases. Resistance was significantly higher in males (64.3%) and in patients aged 61–80 years (p < 0.001). Surgical wards showed greater resistance rates compared to medical departments. A peak in resistance was identified during January–March 2023, particularly for A. baumannii (76.3%). IPM-MEM resistance discrepancies were found in Citrobacter and Proteus species. Gene profiling of resistant strains revealed the predominance of blaNDM, blaVIM in all organism.ConclusionThe findings reveal a high and fluctuating burden of carbapenem resistance, especially in elderly males and surgical settings. Continuous surveillance and targeted interventions are vital to curbing the spread of CR-GNB in high-risk healthcare environments.